Hubungan Regulasi Diri dan Dukungan Sosial dengan Prokrastinasi Akademik pada Siswa di SMAN 1 Sunggal - Pinta Ito Harahap (Universitas Medan Area, 2021)
This study aims to determine the relationship between self-regulation and social support on academic procrastination in SMA N 1 Sunggal students. The study population was 180 students. The research sample was 125 people, the sampling technique was random sampling method. This study uses three psychological scales, namely the Academic Procrastination scale, the social support scale, and the self-regulation scale. Multiple linear regression analysis method techniques. Based on the results of research and calculations of multiple linear regression analysis, it can be seen that (1) There is a significant negative relationship between Self-Regulation (X1) and Student Academic Procrastination (Y) at SMA N 1 Sunggal with a moderate level of correlation where the correlation coefficient value or contribution is 0.436 or 43.6%. (2) There is an insignificant negative relationship between Social Support (X2) and student Academic Procrastination (Y) at SMA N 1 Sunggal with a very low level of correlation, where the correlation coefficient value or contribution is 0.030 or 0.003%. (3) There is a relationship between Self-Regulation (X1) and Social Support (X2) together with Academic Procrastination (Y) in SMA N 1 Sunggal with a moderate level of correlation.